Exploring Gender Disparities in Autism Spectrum Disorders: Prevalence and Symptoms in Malaysia - Hashmi, Shazia Iqbal; Nawi, Nurul Hudani Md; Cosmas, Getrude; Sombuling, Agnes (Developmental and Clinical Psychology, 2024)
In light of the considerable number of cases documented on an annual basis, autism spectrum disorder (ASD) has emerged as a condition with a rising prevalence in recent times. There is a greater prevalence of ASD in males than in females, both in terms of overall incidence and the presentation of symptoms. Additionally, males with ASD tend to exhibit more functional impairments and repetitive behaviors. To gain a deeper understanding of these variations, further research is required. The principal objective of this study is to ascertain whether there are gender disparities in the frequency and symptoms of autism spectrum disorders in Malaysia. The Malay translation of the Autism Spectrum Quotient – Children's Version and the Children's Autism Spectrum Test have been completed by parents or caregivers of fifty-two children between the ages of seven and twelve who have been diagnosed with autism spectrum disorder (ASD). The current research indicates that, in terms of prevalence, there is a ratio of 1:5 in favor of males over females. However, no clear differences were observed between the sexes in terms of ASD symptoms in this study group. Significant advances in the prevention or treatment of autism spectrum disorders in men and women can be achieved through systematic efforts to understand gender differences in the prevalence and symptoms of these diseases in Malaysia.